Relationship between the star and the hotel service guarantees of customer satisfaction - Mohd Shahril, Aslinda; Abdul Aziz, Yuhanis; Othman, Mohhidin; Bojei, Jamil (Canadian Center of Science and Education, 2015)
Earlier research on service guarantees have evidenced the importance of service guarantees, their positive relationship with the firm, enhance customer’s perception and act as a tool to the service quality. The objectives of this study were to examine the relationship between hotel star, service guarantees and customer satisfaction in the luxury hotels in Malaysia. The study wished to explore if hotel star has significant relationship with employee perception and service guarantees and employee perception toward customer satisfaction. The study investigates these relationships from the front-line hotel employee perspective. The study conducted survey and delivered the questionnaires to the front-line employees. The findings indicated that hotel star has strong influence on service guarantees offered by hotels and it has moderate relationship with customer satisfaction. The result showed that customer has almost same level of satisfaction when staying at four or five star hotels due to similar service offerings. Based on the findings, implications for hotel and customers are discussed and further research is suggested.